Does the length of dental implants inserted in areas of inferior alveolar nerve lateralization interfere on mandibular resistance to fracture? - Brackmann, Mariana Schaffer [UNESP]; Padovan, Luis Eduardo Marques [UNESP]; Marcantonio, Elcio [UNESP]; Klüppel, Leandro Eduardo [UNESP] (Wolters Kluwer, 2019)
The aim of this study was to compare, in vitro, the mechanical resistance to vertical displacement of the mandible after osteotomy for lateralization of the inferior alveolar nerve and installation of dental implants. One hundred eighty polyurethane mandibles were equally divided into 6 groups: G1—intact hemi-mandibles (control group), G2—hemi-mandibles after osteotomy for lateralization of the inferior alveolar nerve, G3—hemi-mandibles with installation of 3 bicortical dental implants (3.75 13 mm), G4—hemi-mandibles with installation of 3 dental implants that did not reach the basal cortical bone (3.75 11 mm), G5—hemi-mandibles after osteotomy for lateralization of the inferior alveolar nerve and installation of 3 bicortical dental implants (3.75 13 mm) and G6—hemi-mandibles after osteotomy for lateralization of the inferior alveolar nerve and installation of 3 dental implants that did not reach the basal cortical bone (3.75 11 mm). The specimens were subjected to linear loading tests. The highest mean value of maximum load was found in G1 (412.36N 11.99), followed by G2 (396.87N 23.94), G3 (319.63N 57.28), G4 (303.34N 18.25), G5 (231.75N 63.64) and G6 (228.13N 20.75). Based on this data, it can be concluded that the bicorticalization (or not) of the implants was not a statistically significant risk factor for the vertical displacement of polyurethane hemi-mandibles.
Keywords: Dental implants; Mandible; Postoperative complications